The impact of COVID-19 on route-level changes in transit demand an analysis of five transit agencies in Florida, USA. (January 2023) - Patni, Sagar; Srinivasan, Sivaramakrishnan; Suarez, Juan
Abstract: This study examined the impacts of COVID-19 on changes in route-level transit demand across five transit agencies in the state of Florida. Data for 120 routes from five transit agencies were used to develop two-stage instrumental variable models. Data from January of 2019 to December of 2020 were used in the analysis. Routes that served a greater mix of land-uses experienced a smaller decline in ridership. The impacts of several other land-use variables were, however, not consistent across the five transit agencies. Fare suspension was estimated to have a positive impact on ridership. In contrast, occupancy reduction measures (to promote social distancing within the transit vehicle) had a very strong negative impact on demand. The magnitude of the negative impact of occupancy reduction was larger than the positive impacts of fare suspension. Extending this analysis to a larger set of routes across more agencies would be useful in enhancing the robustness of the findings from our models. Extending our analysis to include data from 2021 and later to capture the recovery phase is also an important direction for future work.